Aluminium Foams in the Design of Transport Means - Grilec, Krešimir; Marić, Gojko; Miloš, Katica (Promet - Traffic&Transportation, 2012)
The requirements for weight reduction and improvement of performances in the design of transport means are often in contradiction to the requirements for increased safety. One of the possible ways of meeting these requirements is the application of metal foams. Thanks to cellular structure of aluminium foam along with low weight, the capability of noise and vibration damping, they feature also excellent capabilities of absorbing impact energy. Their application in the production of impact-sensitive elements of mobile or stationary transport means has significantly contributed to the reduction of the impact or collision consequences. The focus of this paper is on improving the energy absorption characteristics of aluminium foams considering the significance of their application for the technology of traffic and transport. The paper analyzes the influence of the chemical composition and density on the compression behaviour of aluminium foam. The aluminium foam samples were produced from Alulight precursor. The capability of samples to absorb mechanical energy has been estimated according to the results of compression tests. The tests were performed on a universal test machine. The test results showed that aluminium foams feature good energy absorption and the absorption capability decreases with the foam density. The Alulight AlMgSi 0.6 TiH2 - 0.4 foam can absorb more energy than Alulight AlSi 10 TiH2 – 0.8 foam.